Young Couples' Views on Premarital Agreements Reviewed from the Social, Gender and Positive Legal Aspects - Syahri Ramdhan Alfarizi; Yusup Hidayat (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Prenuptial agreement in Indonesia can be understood not only within the framework of positive law, but also from social and gender perspectives. In society, prenuptial agreements are often viewed as a form of protection for economic rights, bargaining positions, and individual autonomy, particularly for women within the household. Social analysis shows that increasing awareness of gender equality encourages couples to negotiate rights and obligations more fairly even before marriage takes place. From a gender perspective, prenuptial agreements function as instruments to prevent the subordination of women, while affirming their rights in managing property and increasingly decisions in marriage. Interviews with couples of productive age individuals that the motivation for drafting prenuptial agreements is not solely related to asset protection but also reflects modern rationality in household relations. In the context of Indonesian positive law, prenuptial agreements are regulated under the Marriage Law and its implementing regulations, thus providing legal legitimacy for such practices. Thus, this study seeks to explain prenuptial agreements as a social phenomenon, an instrument of gender equality, and a legally recognized practice within the legal system.